Monsters : a fan's dilemma - Dederer, Claire, 1967- (New York : Alfred A. Knopf, 2023)
"In this unflinching, deeply personal book that expands on her instantly viral Paris Review essay, "What Do We Do With the Art of Monstrous Men?" Claire Dederer asks: Can we love the work of Hemingway, Polanski, Naipaul, Miles Davis, or Picasso? Should we love it? Does genius deserve special dispensation? Is male monstrosity the same as female monstrosity? Does art have a mandate to depict the darker elements of the psyche? And what happens if the artist stares too long into the abyss? She explores the audience's relationship with artists from Woody Allen to Michael Jackson, asking: How do we balance our undeniable sense of moral outrage with our equally undeniable love of the work? In a more troubling vein, she wonders if an artist needs to be a monster in order to create something great. And if an artist is also a mother, does one identity inexorably, and fatally, interrupt the other? Highly topical, morally wise, honest to the core, Monsters is certain to incite a conversation about whether and how we can separate artists from their art"--.
Prologue: The Child Rapist -- Roll Call -- The Stain -- The Fan -- The Critic -- The Genius -- The Anti-Semite, the Racist, and the Problem of Time -- The Silencer and the Silenced -- The Anti-Monster -- Am I a Monster? -- Abandoning Mothers -- Lady Lazarus -- What Do We Do with the Art of Monstrous Women? -- Drunks -- The Beloveds.
"A Borzoi book."
Includes bibliographical references.
Keywords: Arts and morals; Artists -- Conduct of life